Effect of some heat treatments on anelastic properties of Ti-15Zr-xMo alloys - Correa, Diego Rafael Nespeque [UNESP] (2016)
Ti and Ti-based alloys have favorable properties for biomedical applications, such as high specific strength, low Young’s modulus, excellent corrosion and wear resistance, and good biocompatibility. The addition of alloying elements and heat treatments can result in a good combination of properties. Mo and Zr are β-stabilizer elements that decrease the Young’s modulus and increase the mechanical strength and corrosion resistance. Oxygen is an interstitial element that can improve mechanical strength and prevent ω phase formation. In this study, we analyzed the influence of substitutional and interstitial elements, and some heat treatments in the crystalline structure, microstructure and selected mechanical properties (Vickers microhardness, Young’s modulus and internal friction) of Ti-15Zr-xMo (5, 10, 15 and 20 wt%) alloys. The alloys exhibited dependence on the alloying elements and heat treatments, which resulted in different structural and microstructural changes. The mechanical properties were dependent on phase transformations induced by the compositions and heat treatments.